ANALISIS JALUR (PATH ANALYSIS) UNTUK MENGETAHUI HUBUNGAN ANTARA USIA IBU, KADAR HEMOGLOBIN, DAN MASA GESTASI TERHADAP BERAT BAYI LAHIR (Studi Kasus di Rumah Sakit Aisyiyah Kudus) - Handaningrum, Evi Yulia; Safitri, Diah; Ispriyanti, Dwi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Birth weight is the weight of a baby who weighed in 1 (one) hour after birth. Birth weight is important to note because many cases are caused by birth weight that is too high or too low as in the case of LBW (Low Birth Weight). LBW is infants with a birth weight less than 2500 grams. The factors that considered in addressing LBW are factors maternal age, maternal hemoglobin levels, and gestational age. One of the statistical analysis that can be used to analyze the causal relationship of several variables is path analysis.Path analysis is a modified form of regression analysis in which the independent variables studied not only directly affect the dependent variable, but it can also affect these variables indirectly. The independent variables have a direct effect and indirect effect on the dependent variable. Based on analyzing, it is concluded that the variable which has a direct effect to birth weight infant was gestational age, whereas for maternal age and maternal hemoglobin levels effect to birth weight infant, it can be seen by its inderect effect.